PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF VIRTUAL (MIVi) MELALUI APLIKASI MANUFAKTURMUDAH - Lies Nurhaini; Kus Indrani Listyoningrum; Sudiyanto Sudiyanto; Sigit Santosa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Technology has an important role for education in Indonesia. The demands of improving the quality of education to support the development in Indonesia can be facilitated with technology. In fact, technological advances in the world are a challenge for Indonesia to follow. There is a pandemic that hit the world, requiring Indonesia to conduct online learning. Learning in the network through information and communication technology. However, online learning with certain subjects is poorly understood by students. For example, accounting subjects about manufacturing companies. In order to solve the problem of understanding the material that students feel, researchers created the Application ManufakturMudah. The app was successfully developed with a variety of interesting features for users. This research was conducted to find out how well the ManufakturMudah application performs. This research method uses Research and Development with the help of several respondents.